Microcrystalline Cellulose for Delivery of Recombinant Protein-Based Antigen against Erysipelas in Mice - Jeon, Wooyoung (Biomed Res Int, 2018)
The study describes the development of a vaccine using microcrystalline cellulose (Avicel PH-101) as a delivery carrier of recombinant protein-based antigen against erysipelas. Recombinant SpaA, surface protective protein, from a gram-positive pathogen Erysipelothrix rhusiopathiae was fused to a cellulose-binding domain (CBD) from Trichoderma harzianum endoglucanase II through a S3N10 peptide. The fusion protein (CBD-SpaA) was expressed in Escherichia coli and was subsequently bound to Avicel PH-101. The antigenicity of CBD-SpaA bound to the Avicel was evaluated by enzyme-linked immunosorbent (ELISA) and confocal laser scanning microscope (CLSM) assays. For the examination of its immunogenicity, groups of mice were immunized with different constructs (soluble CBD-SpaA, Avicel coated with CBD-SpaA, whole bacterin of E. rhusiopathiae (positive control), and PBS (negative control)). In two weeks after immunization, mice were challenged with 1x10(7) CFU of E. rhusiopathiae and Avicel coated with CBD-SpaA induced protective immunity in mice. In conclusion, this study demonstrates the feasibility of microcrystalline cellulose as the delivery system of recombinant protein subunit vaccine against E. rhusiopathiae infection in mice.